Piezoelectric MEMS microphones based on rib structures and single crystal PZT thin film - Zhiwei You; Jinghan Gan; Chong Yang; Renati Tuerhong; Lei Zhao; Yipeng Lu (Microsystems & Nanoengineering)
Abstract In this study, a controllable mass‒frequency tuning method is presented using the etching of rib structures on a single-crystal PZT membrane. The rib structures were optimized to reduce the membrane mass while maintaining the stiffness; therefore, the center frequency could be increased to improve the low-frequency bandwidth of microphones. Additionally, this methodology could reduce the modulus and improve the sensitivity for the same resonant frequency, which typically indicates the maximum acoustic overload point (AOP). The PZT film was chosen because of its greater density; the simulation results showed that PZT could provide a greater frequency tuning (24.9%) compared to that of the AlN film (5.8%), and its large dielectric constant enabled the optimal design to have small electrodes at the maximum stress location while mitigating the sacrificial capacitance effect on electrical gain. An analytical model of rib-structure microphones was established and greatly reduced the computing time. The experimental results of the impedance tests revealed that the center frequencies of the six microphones shifted from 74.6 kHz to 106.3 kHz with rib-structure inner radii ranging from 0 μm to 340 μm; this result was in good agreement with the those of the analytical analysis and finite element modeling. While the center frequency greatly varied, the measured sensitivities at 1 kHz only varied within a small range from 22.3 mV/Pa to 25.7 mV/Pa; thus, the membrane stiffness minimally changed. Moreover, a single-crystal PZT film with a (100) crystal orientation and 0.24-degree full width at half maximum (FWHM) was used to enable differential sensing and a low possibility of undesirable polarization. Paired with a two-stage differential charge amplifier, a differential sensing microphone was experimentally demonstrated to improve the sensitivity from 25.7 mV/Pa to 36.1 mV/Pa and reduce the noise from −68.2 dBV to −82.8 dBV.